2004
DOI: 10.3736/jcim20040208
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of non-small-cell lung cancer with chemotherapy and Sansheng Huatan Decoction

Abstract: Sansheng Huatan Decoction combined with chemotherapy is a better treatment for non-small-cell lung cancer as compared with chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The information in these ten trials including incidence rate, severity, and concentrations of blood count indicated that adverse reactions reported were toxicities associated with conventional treatment that the participants in both groups received commonly, not associated with HM. Three trials reported no between‐group differences (Zhuang et al, ; Xie et al, ; Jiang et al, ), while seven trials found significant positive findings on combined HM‐conventional treatment group for partial adverse reactions comparing with control group (Xiao and Yang, ; Wu et al, ; Hou and Lu, ; Zhuang et al, ; Fang et al, ; Chan et al, ; Lin et al, ). The adverse reactions reported in both intervention and control groups were neutropenia, leukopenia, anemia, thrombocytopenia, nausea and vomiting, diarrhea, stomatitis, salivary gland change, anorexia, abdominal distension, hearing impaired, cutaneous change, neuropathy, fever, and hepatic, renal, and cardiac adverse reactions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The information in these ten trials including incidence rate, severity, and concentrations of blood count indicated that adverse reactions reported were toxicities associated with conventional treatment that the participants in both groups received commonly, not associated with HM. Three trials reported no between‐group differences (Zhuang et al, ; Xie et al, ; Jiang et al, ), while seven trials found significant positive findings on combined HM‐conventional treatment group for partial adverse reactions comparing with control group (Xiao and Yang, ; Wu et al, ; Hou and Lu, ; Zhuang et al, ; Fang et al, ; Chan et al, ; Lin et al, ). The adverse reactions reported in both intervention and control groups were neutropenia, leukopenia, anemia, thrombocytopenia, nausea and vomiting, diarrhea, stomatitis, salivary gland change, anorexia, abdominal distension, hearing impaired, cutaneous change, neuropathy, fever, and hepatic, renal, and cardiac adverse reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The proportions of NK cells increased in 12 studies, seven of which demonstrated statistical significance, in patients treated with HM plus conventional medicine compared with those treated with conventional medicine alone (Jia et al, ; Hou and Lu, ; Zhang et al, ; Fang et al, ; Jiang et al, ; Gao et al, ; Lin et al, ). There was a smaller decrease in absolute NK cell counts after conventional treatment combined with HM in two studies (Zhuang et al, ; Chan et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations